Genesis and geological significance of the mafic rocks in the paleoproterozoic Lieryu formation, Liaoning - Chen, Jingsheng; Li, Linchuan; Li, Bin; Tian, Yi; Zhang, Chao; Zang, Yanqing; Zhao, Yan (Frontiers in Earth Science, 2025)
IntroductionThe Jiao-Liao-Ji Belt (JLJB), situated between the Longgang Block and Nangrim Block, hosts extensive Paleoproterozoic metasedimentary-volcanic sequences of the Liaohe Group. There has always been controversy over the stratigraphic relationships between the various formations of the Liaohe Group and the tectonic evolution of the JLJB.MethodsField investigations, petrology, zircon U-Pb dating, and whole-rock geochemistry.ResultsThe mafic rocks from the Lieryu Formation comprises gabbro and amphibolites. Zircon U-Pb geochronology yields crystallization ages of ca. 2052 ± 15 Ma, 2089 ± 55 Ma, 2053 ± 28 Ma, and 2,190 ± 13 Ma, which reconstruct the geochronological framework of Lieryu mafic magmatism to 2,190–1995 Ma. The average SiO2 content of samples ranges from 48.11 wt% to 50.47 wt%, which indicates mafic rocks. The K2O content of samples varies from 0.81 wt% to 1.44 wt% respectively, indicating calc-alkaline to high-K calc-alkaline series. The value of Mg# ranges from 45.93 to 57.10.DiscussionThe chronology of volcanic rocks cross different formations of the Liaohe Group exhibiting no systematic stratigraphic progression but rather interfingering relationships. Combined with field observations of mélange associated with boron deposits within the Lieryu Formation, it is believed that the Liaohe Group is not coherent stratigraphic succession, but a disordered tectonic stratigraphic unit. The results of trace element show that the Paleoproterozoic mafic rocks originated from a transitional mantle source, and three of them (D1902, D1905 and D1911) are mainly influenced by metasomatism, while the D1914 influenced by dual fluid and melt in the source. The D1902, D1905 and D1914 are product of partial melting of amphibole-bearing spinel lherzolite, leading to residual hornblende and spinel in the source. The D1911 is from partial melting of garnet–spinel lherzolite with the 50:50 ratios of garnet and spinel and 6:1 ratio of clinopyroxene to garnet, resulting in garnet and spinel left in the source. During the ascent and emplacement, assimilation and contamination occurred between mafic magmas and continental crustal materials. Geochemical data from the Lieryu mafic rocks reveal that D1902 (amphibolite) and D1914 (gabbro) show the same characteristics with island arc basalt (IAB), indicating an island arc environment. D1905 (amphibolite) and D1911 (gabbro) show the same characteristics with mid-ocean ridge basalt (MORB), and were formed in a mid-ocean ridge environment. These evidences indicate an ancient ocean existed in the Paleoproterozoic. The JLJB represents a collisional orogen formed during the closure of the Paleoproterozoic oceanic basin.